Diagnóstico de los costos de prevención y evaluación para mejorar el proceso del enrollado de manjar de Dulcería Marialy de Calceta - Quijije Vera, Diana Carolina (2014)
The topic of research was conducted in the Dulcería Marialy to detect flaws that were immersed in the process of developing the coiled delicacy , diagnosing the causes affecting the production of the product , on the other hand issues , criteria, and definitions that were consulted through different authors of scientific profile that helped to support the implementation of the research; methods and techniques also provided necessary information about microenterprise that were used, plus tools ( Kendall, Pareto Diagram , Brainstorming and Cause-Effect Diagram ) where the affected items were determined in the process of the product applied, and developed steps necessary to fulfill the objectives in research through the procedure performed on the stages of the methodological design, major problems that the process of making coiled delicacy, determining which were obtained are the possible causes of this problem , and the consequences that might exist if corrective measures if not taken. To terminate the respective research conclusions and recommendations relate to the objectives proposed in the object of study were conducted and concluded that the diagnosis was made small industry there are no standards of materials and time to affect production costs through this problem the authors of this issue developed a proposal to improve the legal representative of sweets to take preventive measures for reducing or eliminating problems diagnosed.